FENOMENA FUJOSHI PENGGEMAR YAOI PADA MAHASISWA PRODI SASTRA JEPANG DI BANDUNG: STUDI KASUS - muhlisian, asepachmad; Putri, Nurul Inaya (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2026)
This study analyzes the phenomenon of fujoshi (yaoi fans) among Japanese Literature students in Bandung. The purpose of this study is to identify how the fujoshi phenomenon emerged and developed among Japanese Literature students in Bandung and to identify the factors that influence students to become yaoi fans. The method used in this study is qualitative with a case study approach. Data collection techniques used in this study were participatory observation and in-depth interviews. The results of this study from 8 respondents indicate that interest in the yaoi genre generally began in high school, some even since junior high through media such as anime, manga, fan art, and platforms such as Twitter, TikTok, Instagram, Wattpad, and Discord. This interest often occurs accidentally and develops. Reading the yaoi genre helps them recognize themselves as fujoshi, which becomes a form of self-expression even though it is considered taboo by society. Influencing factors include interesting stories, visuals, an escape from daily activities, and the influence of Japanese popular culture. Although many choose to remain closeted due to stereotypes, most still enjoy this interest as long as it doesn't interfere with their social life. Keywords: Phenomenon, Fujoshi, Yaoi, students